2021
DOI: 10.1063/5.0040552
|View full text |Cite
|
Sign up to set email alerts
|

Size- and temperature-dependent Young's modulus of SiC nanowires determined by a laser-Doppler vibration measurement

Abstract: Young's modulus of Fe-catalyzed silicon carbide (SiC) nanowires was measured in the temperature range of 300–575 K by the use of a laser Doppler vibrometer. The nanowires have a face-centered cubic structure grown along the [111] direction and exhibit different cross-sectional geometries, including circle, rectangle, hexagon, ellipse, trapezoid, and triangle. When the effective diameters of the nanowires decrease from 200 to 55 nm, their room-temperature Young's modulus decreases from ∼550 GPa (the bulk value)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Note that the cross‐sectional profile was obtained after the TEM characterization, by fracturing the nanowire cantilever near the frame edge by a W tip under the optical microscope and then acquiring at an angle of ≈5° deviated from its axial direction. [ 17,18 ] High‐resolution TEM analysis further revealed that, after the test at elevated temperatures, the edge of the nanowire changed to an amorphous structure, while the core still had a crystalline structure, as shown in Figure 2i. This suggests a crystalline–amorphous transition might initiate at the surface, and then extend into the core.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Note that the cross‐sectional profile was obtained after the TEM characterization, by fracturing the nanowire cantilever near the frame edge by a W tip under the optical microscope and then acquiring at an angle of ≈5° deviated from its axial direction. [ 17,18 ] High‐resolution TEM analysis further revealed that, after the test at elevated temperatures, the edge of the nanowire changed to an amorphous structure, while the core still had a crystalline structure, as shown in Figure 2i. This suggests a crystalline–amorphous transition might initiate at the surface, and then extend into the core.…”
Section: Resultsmentioning
confidence: 99%
“…Note that α ( T ) is considered the same as the bulk value of 21 ppm K −1 . [ 27 ] The TCE value is much greater than the corresponding value of −(47.4–78.1) ppm K −1 for SiC nanowires with diameters of 55 to 200 nm, [ 17 ] slightly greater than the value of −108.7 ppm K −1 for ZnO nanowires with diameters of 101 to 350 nm, [ 16 ] and significantly smaller than the value of (410–449) ppm K −1 for metal Ag microwhiskers. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations